Effect of Washed Process Fermentation on Specialty Coffee Flavor - Ridwan Rizkyanto; Bastian Nova; Linda Wati; Padriasyah Lubis (UPN Veteran Jatim, 2026)
Specialty coffee represents a high-value agricultural commodity whose overall quality is profoundly influenced by post-harvest processing parameters, with fermentation constituting a critical determinant in the development of its distinctive sensory profile. Among various processing techniques, the washed process, characterized by controlled wet fermentation has been widely recognized for its capacity to generate unique and refined flavor attributes. The present study sought to investigate the influence of differential fermentation durations within the washed process framework on the sensory characteristics of Arabica specialty coffee. A sensory evaluation was conducted using the standardized cupping test in accordance with Specialty Coffee Association (SCA) protocols, employing trained panelists to assess multiple flavor dimensions. Analytical observations indicated discernible variations in sensory attributes as a function of fermentation duration, thereby reinforcing the necessity of stringent quality control measures with particular emphasis on fermentation management. These insights highlight the pivotal role of optimizing fermentation time in enhancing flavor complexity while mitigating the emergence of undesirable off-flavors. It is further recommended that subsequent research endeavors explore the targeted application of defined microbial starters in conjunction with the systematic optimization of fermentation parameters, in order to advance both the consistency and the sensory excellence of specialty coffee production.